Reminiscences of the Art of Dance in Jesuit Literature - Reglińska-Jemioł, Anna (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
The achievements of a school dance seem original and valuable. It was said that: There is no one like theJesuits for doing pirouettes. Also in France three of the ballet masters — Beauchamps, Pécour, and Dupré— worked for the Jesuits and were directors of the Royal Academy, which became later the Paris Opéra.The art of dancing, and in particular ballet, is a field, thanks to which, the distinct and unique natureof the Jesuit college theatre can be depicted against the background of the theatrical map of the 18th century.Terpsichore did not solely serve the purposes of entertainment, but was perceived as a perfect toolin the cultivating of higher values (such as science, faith, patriotism, or morality) or in the propagatingof a defined model of behaviour. Such an attitude can be observed at all stages of the development of theart of dance — from ceremonial rituals, through choreographic interludes, i.e. somersaults and leaps, andfull pantomimes, to completely independent ballets with plot and action. Among their propagators andcreators was Gabriel Le Jay, whose treatise Liber de choreis led dance in school theatres onto a new road.In Poland from the middle of the 18th century we have four printed programmes of Jesuit performancesof ballets with action. Ballets latter appeared on the boards of school theatres together with the theatricalreform and are undoubtedly a novelty in the repertoire of the middle of the 18th century. Although theyare based on Baroque emblematic constructions, there can be noticed in these realisations an attemptto imitate nature and an emphasis on the artistic and imaginative form of the spectacle. These elementsconstitute important points in Noverre’s reform of dance. Surprisingly, when writing about dance webecome aware of the overlapping history. The cultural world was changing and this was reflected in thedance or ballets of the day.